Avaliação do hidrogel de celulose bacteriana na cicatrização de feridas em equinos - Faria, Ana Paula Prado Antunes de (2021)
Horses are predisposed to trauma and the resulting wounds usually heal by second intention, with complications in this process, such as the formation of exuberant granulation tissue, being common. The biocellulose-based hydrogel is a new therapeutic possibility for the treatment of wounds in both human and equine medicine. Biocellulose or bacterial cellulose is a biopolymer produced by nanotechnology that has properties that aid in the healing of epithelial wounds. The aim of the present study was to evaluate the topical use of hydrogel based on 1% biocellulose in experimental wounds performed on horses. Experimental wounds were performed in the lumbar region (4 cm2) on 4 healthy adult horses. In the wounds of the control group, the dressing was applied only with 0.9% saline solution and the wounds of the treated group received hydrogel based on 1% biocellulose. Skin wound biopsies were performed 3, 7, 14 and 21 days after the surgical procedure. Macroscopic analyzes referring to the wound area and contraction rate were performed. Microscopic and molecular analyzes of gene expression of cytokines (IL-6, IL-10, TNF-α and TGF-β) and collagen (type I and type III) using the RT-qPCR technique after isolation of RNA from biopsy samples of fabric, treated or not with biocellulose hydrogel. The results of the analyzes compared at each evaluated moment whether or not there was a significant between the treatments. The macroscopic and microscopic evaluation revealed that the use of the hydrogel was beneficial in terms of the best aspect of the new scar tissue formed and its anti-inflammatory cell effect. The molecular evaluation did not show any statistical difference between the groups at any of the moments evaluated. Thus, the preliminary data of this study allow to affirm that the biocellulose hydrogel is an alternative in the treatment of wounds in horses, being necessary to continue the researches that investigate its molecular action in the healing of wounds in horses.